2020
DOI: 10.1021/jacs.9b13584
|View full text |Cite
|
Sign up to set email alerts
|

Helical Assemblies of One-Dimensional Supramolecular Polymers Composed of Helical Macromolecules: Generation of Circularly Polarized Light Using an Infinitesimal Chiral Source

Abstract: We report the synthesis of one-dimensional supramolecular polymers composed of one-handed helical macromolecules bearing fluorescent pendant groups and the generation of circularly polarized light on the basis of hierarchical chiral amplification starting from a tiny amount of chiral substituent. Copolymerization of benzo­[1,2-b:4,5-b′]­dithiophene-appended achiral/chiral isocyanides (99:1, mol/mol) with a solid-state photoluminescence feature afforded submicrometer supramolecular fibers, in which almost perfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 85 publications
0
73
0
Order By: Relevance
“…[25][26][27] These studies not only explore the structures and functions of their natural counterparts,but also and more importantly,develop new functional materials with applications in, for example,c hiral resolution, [28] asymmetric catalysis, [29,30] chiral switch, [31,32] and circularly polarized luminescence (CPL). [33,34] Among them, CPL has lately attracted increasing attentions on account of their potentials in chemical sensors,biological probes,and three-dimensional displays. [35][36][37][38] Several kinds of CPL materials have been developed based on small organic molecules,l anthanide and transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] These studies not only explore the structures and functions of their natural counterparts,but also and more importantly,develop new functional materials with applications in, for example,c hiral resolution, [28] asymmetric catalysis, [29,30] chiral switch, [31,32] and circularly polarized luminescence (CPL). [33,34] Among them, CPL has lately attracted increasing attentions on account of their potentials in chemical sensors,biological probes,and three-dimensional displays. [35][36][37][38] Several kinds of CPL materials have been developed based on small organic molecules,l anthanide and transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33–35 ] Recently, Ikai's group reported that the helical supramolecular polymers were assembled as a cholesteric liquid crystal, strong chiral amplification effect, and intense CPL signal ( g em = 1.0 × 10 −2 ) were observed while adding infinitesimal achiral dyes into cholesteric LC to form N*‐LCs. [ 36 ] In 2019, Duan and co‐workers explored a new pathway to develop the novel CPL‐active LC material by dispersing chiral emitters and a triplet donor into N‐LCs, the g em of N*‐LCs could be amplified one order of magnitude up to about 0.04 through remarkable photon upconverted circularly polarized luminescence (UC‐CPL) mechanism. [ 37 ]…”
Section: Methodsmentioning
confidence: 99%
“…Thus, PLLA and PDLA are ideal polymers for the study of the extrinsic Cotton effect or induced Cotton effect involving the interaction of helical polymer structure in solution with a guest molecular chromophore hosted inside the spiral pitches or intercalated between the PLLA helices. The guest symmetric molecule without ORD signal, by interacting with the asymmetric helical structure of PLLA, gives rise to an induced ORD signal in correspondence of its electronic transition in the visible through the coupled oscillator mechanism or the one-electron mechanism or exciton coupling [21][22][23][24][25]. In other words, the electronic transition of the chromophore of the guest molecule has a spatial relationship with host macromolecule which is manifested as a dissymmetry in the ORD spectrum of the complex [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The guest symmetric molecule without ORD signal, by interacting with the asymmetric helical structure of PLLA, gives rise to an induced ORD signal in correspondence of its electronic transition in the visible through the coupled oscillator mechanism or the one-electron mechanism or exciton coupling [21][22][23][24][25]. In other words, the electronic transition of the chromophore of the guest molecule has a spatial relationship with host macromolecule which is manifested as a dissymmetry in the ORD spectrum of the complex [21][22][23][24][25]. The induced Cotton effect was indeed detected by ORD spectroscopy both in solutions of PLLA/iodine [26] and PLLA/C 60 fullerene [27], whereas a charge-transfer host-guest interaction was measured in both cases.…”
Section: Introductionmentioning
confidence: 99%